Emerging Regional Security Architecture in the Middle East- Post Arab Spring Period - Muhammad Faisal (CISS Insight Journal, 2014)
The popular demonstrations manifest– what was dubbed as “Arab Spring”, coupled with the responses of the governments in power and the ensuing political changes in the Middle East, have had critical implications for regional security and stability. These uprisings shook the foundations of regional political landscape and have left deep marks on the political culture of the Middle East. The Middle East has been in transition since late 2010. The large-scale demonstrations across Arab states sparked by self-immolation of a street vendor in Tunisia had wide ranging impact on the politics of the region. The wave of mass protests, spreading from Tunisia to other neighboring states, has been termed ‘Arab Spring’. These uprisings brought dramatic transformations in four states: Tunisia, Egypt, Libya and Yemen. In the wake of these developments political upheavals were set in motion in other states as well. The regime in power in Bahrain was undermined; stability of Saudi Arabia was threatened; and most crucially it unleashed a civil war in Syria which continues unabated. The rest of the regimes in power in other Arab states have been shaken, momentarily, at the very least. These revolutions, popular movements or uprisings, however they may be described, are arguably the most significant development in the regional politics of Middle East in decades.